Respuesta:
Explicación paso a paso:
A=(-1)÷(3×()+
A=()÷(3×√3)
A=()÷()
A=
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
Respuesta:
Explicación paso a paso:
A=(
-1)÷(3×(
)+![\frac{1}{2} \frac{1}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B1%7D%7B2%7D)
A=(
)÷(3×√3)![+\frac{1}{2} +\frac{1}{2}](https://tex.z-dn.net/?f=%2B%5Cfrac%7B1%7D%7B2%7D)
A=(
)÷(
)
A=![\frac{-1\sqrt{3} }{6\sqrt{3}+1 } \frac{-1\sqrt{3} }{6\sqrt{3}+1 }](https://tex.z-dn.net/?f=%5Cfrac%7B-1%5Csqrt%7B3%7D+%7D%7B6%5Csqrt%7B3%7D%2B1+%7D)